Influence of Digital Marketing Communication: Gen Zers Behavioural Perspective - Maheswari, M Uma; Jose, Biji (Ushus Journal of Business Management, 2024)
Digital marketing communication involves the strategic use of various online channels and platforms to convey messages, promote products or services, and engage with target audiences. This multifaceted approach includes strategies such as search engine optimization (SEO), content marketing, social media marketing, email marketing, pay-per-click (PPC) advertising, display advertising, mobile marketing, video marketing, and data analytics. By using these digital channels effectively, businesses can increase brand visibility, drive website traffic, generate leads and ultimately increase sales. Success in digital marketing communications is centered on understanding audience preferences, crafting compelling content, using data insights to optimize, and maintaining a dynamic online presence that resonates with customers. Gen Z, also known as Zoomers, refers to the demographic group born roughly between 1996 and 2010s, succeeding Millennials and preceding Generation Alpha. This generation is characterized by having grown up in a digitally connected world where smartphones, social media and instant access to information are common aspects of their lives from a young age. Gen Z individuals are often described as technological, socially conscious, with a preference for authenticity and meaningful experiences. Understanding the unique characteristics, preferences and behaviours of Gen Z is essential for businesses and marketers looking to engage with this generation effectively. The present study is descriptive in nature. Data has been collected from both Primary & Secondary sources. Data has been collected from 81 respondents. Descriptive statistics, Chi-square test & Fried man Ranking were used for the present study. The study concluded that there is a significant impact on digital marketing communication on Gen Z buying behaviour.